Pure laparoscopic radical heminephrectomy for a large renal-cell carcinoma in a horseshoe kidney - Rebouças, Rafael Batista (2013)
Introduction Horseshoe Kidneys are the most common renal fusion anomaly. When surgery is contemplated for renal-cell carcinoma in such kidneys, aberrant vasculature and isthmusectomy are the major issues to consider. We describe a case of a pure laparoscopic radical heminephrectomy with hand-sewn management of the isthmus for a 11 cm tumour in a horseshoe kidney. Presentation A 47-year-old man complaining of palpable left flank mass for two months. Magnetic resonance of the abdomen revealed a 11 cm renal mass arising from the left moiety of an incidentally discovered horseshoe kidney. Preoperative CT angiography revealed a dominant anterior renal artery feeding the upper and midpole, with two other arteries feeding the lower pole and isthmus. The patient was placed in a modified flank position. A four-port transperitoneal technique was used, the colon was reflected. Renal pedicle was dissected and the renal arteries and renal vein were secured with polymer clips. The kidney was fully mobilized and a Satinsky clamp was placed on the isthmus for its division. A running 2-0 vicryl hand-sewn was used for parenchyma hemostasis. The specimen was extracted intact in a plastic bag through an inguinal incision. Results The operative time was 220 minutes, and the estimated blood loss was 200 mL. There were no immediate or delayed complications. The patient resumed oral intake on postoperative day 1 and was discharged on postoperative day 2. Pathologic examination of the specimen confirmed a 11 cm organ-confined chromophobe renal-cell carcinoma, with negative margins. Discussion Laparoscopic oncologic surgery in patients with horseshoe kidneys can be technically challenging. The presence of a large cancer in a horseshoe kidney should not preclude a purely laparoscopic approach. With the aid of a Satinsky clamp, the isthmus can be sharply divided and sutured in a fashion similar to the open technique. To our knowledge, this report represents the largest cancer (11 cm) removed laparoscopically in the context of a horseshoe kidney.